2015
DOI: 10.1371/journal.pone.0139388
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Allergy Is a Risk Factor for Endometriosis: An 11-Year Population-Based Nested Case-Control Study

Abstract: BackgroundA cross-sectional study has reported that nickel allergy is associated with endometriosis. However, causal studies of this association are limited.ObjectiveThe objective of this study was to compare the prevalence of nickel allergy in women with and without endometriosis.MethodsWe used a National Health Insurance Service (NHIS) sample cohort dataset that included approximately 1 million individuals from South Korea; the data were obtained between January 01, 2002, and December 31, 2013. We selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…Furthermore, the participants of this study may include patients with dysmenorrhea symptoms such as pelvic pain and excessive menstruation, and infertility. There are some reports that endometriosis is related to infertility, pain, socioeconomic condition, stress, nickel allergy, vitamin D intake [ 39 42 ], and these potential confounding factors cannot be excluded completely with only the variabilities that we adjusted. However, owing to the small sample size of this study, it was difficult to adjust for all of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the participants of this study may include patients with dysmenorrhea symptoms such as pelvic pain and excessive menstruation, and infertility. There are some reports that endometriosis is related to infertility, pain, socioeconomic condition, stress, nickel allergy, vitamin D intake [ 39 42 ], and these potential confounding factors cannot be excluded completely with only the variabilities that we adjusted. However, owing to the small sample size of this study, it was difficult to adjust for all of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…In human health, nickel in watches and jewellery has long been associated with eczema and contact dermatitis, and nickel contained in foods has been recently reported as responsible for weight gain, metabolic abnormalities and carcinogenicity [6] , [7] , [8] , [9] , [10] , [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal symptoms in endometriosis may also be related to IBS or IBS-like disorders [45]. Recent studies showed a higher prevalence of Ni skin allergy in women with endometriosis, as well as a possible Ni involvement in its etiopathogenesis [20,46,47]. On these bases, it is possible to hypothesize that an IBS-like disorder, such as Ni ACM, may be the cause or contributing factor of gastrointestinal symptoms in women with endometriosis.…”
Section: Gastrointestinal Disorders and Endometriosismentioning
confidence: 99%